The Effect of Using Canva-Based Media Usage on Geography Learning Outcomes of Class X Students at UNPATTI Laboratory High School - Asrul; Partini, Dwi (Universitas Veteran Bangun Nusantara, 2024)
This study aims to determine the effect of using Canva digital media on the geography learning outcomes of tenth-grade students on the lithosphere material at UNPATTI Laboratory High School. This research employs an experimental method with a control group and an experimental group design. The research sample consists of 28 students divided into two groups: the control group, which used conventional learning methods, and the experimental group, which used Canva. The results of the independent t-test shown in the table indicate a significant difference between the learning outcomes of the control group and the experimental group. The Levene's Test showed an F value of 0.804 with a significance value (Sig.) of 0.378, indicating that the assumption of equal variances is acceptable. In the t-test for mean comparison, the obtained t value was -2.651 with degrees of freedom (df) of 26 for the assumption of equal variances, and 25.547 for the assumption of unequal variances. The two-sided significance value, which was less than 0.05 (0.013 and 0.014 respectively), indicates a significant difference between the two groups. The mean difference between the two groups was -5.857, showing that the learning outcomes of the control group were significantly lower than those of the experimental group. The results of the independent t-test showed a significant difference between the learning outcomes of the two groups, with the experimental group showing higher learning outcomes. These findings suggest that using Canva as a learning tool can enhance learning outcomes for tenth-grade students on lithosphere material. This study supports the literature stating that interactive technology-based learning approaches can positively impact learning outcomes. Therefore, the use of Canva in learning can be considered an effective strategy to improve educational quality.